Answer:
a = (x - b)/2
Step-by-step explanation:
2a + b = x
-b -b
2a = x - b
/2 /2
a = (x - b)/2
for ex:
x = 3
b = 2
a = ((3) - (2))/2 = 0.5
a = 0.5
2a + b = x
2(0.5) + 2 = 3
Answer:
Hello! Your answer is 71.
Step-by-step explanation:
(48+59+62+71) =240
240 ÷ 4 = 60.
The 4 is the four different points he got.
The 60 is the average percent.
HOPE THIS HELPS!
Answer:
Answer is 116
Step-by-step explanation:
12(10)-4 is 116
It is the same beacuse x is equal to y so x and y both equal 22
Answer:
16a - 6b + 6
Step-by-step explanation:
5a + 5b - 5 + 11a - 11b + 11 = 5a + 11a + 5b - 11b - 5 + 11 = 16a - 6b + 6